Classification of Some Medicinal Plants (Asteraceae) in Badia Al Muthanna, Iraq - Jasim, Haider Mahmod (American Journal of Botany and Bioengineering, 2026)
The Asteraceae family is one of the largest plant families with high species diversity, including about 23,000 species under 1,620 genera. This study aimed to classify and identify some medicinal plant species under the Asteraceae family in the desert of Al-Muthanna, southern Iraq, by using morphological and taxonomic characteristics. In different locations for the Badia Al-Muthanna, field surveys were carried out, and plant samples were collected using random sampling. The voucher specimens containing vegetative and reproductive plant parts were recorded and identified based on morphological features, including habitat, stem type, leaf morphology and shape, inflorescence type, flower color, and fruit type. Some diagnostic traits, such as aromatic test, hairy surfaces, ray florets, pappus presence, and latex production, were also examined. A total of nine medicinal Asteraceae species were identified and classified, namely Aaronsohnia factorovskyi, Achillea santolina, Anthemis deserti, Artemisia herba-alba, Artemisia scoparia, Calendula arvensis, Launaea capitata, Launaea mucronata, and Pulicaria sp. The morphological analysis revealed major phenotypic diversity between the studied species and explained distinct ecological adaptations to desert conditions. Cluster analysis grouped the species into four principal clusters according to similar morphological and diagnostic traits. Artemisia and Launaea species exhibit a strong taxonomic relationship. The aromatic and herbal characteristics were recognized among several species, reflecting their medicinal significance. This study provides valuable taxonomic and diversity information regarding medicinal Asteraceae species in the Badia of Al-Muthanna and establishes a scientific foundation for future pharmacological and taxonomic studies in Iraqi desert ecosystems.